1997
DOI: 10.1016/s0022-5347(01)65086-9
|View full text |Cite
|
Sign up to set email alerts
|

Estramustine Phosphate Versus Placebo as Second Line Treatment After Orchiectomy in Patients With Metastatic Prostate Cancer: Daproca Study 9002

Abstract: Although this study did not prove estramustine phosphate to be superior to placebo in terms of protocol end points, it generates the hypothesis that prolonged survival may be achieved with estramustine phosphate treatment in a subgroup of patients and that this may be predicted by a decrease in PSA after 1 month of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…The combination therapies therefore appear superior for HRPC than EMP monotherapy based on both PSA levels and measurable disease response. A Danish study (DAPROCA study 9002) [12] of EMP versus placebo as second-line treatment after orchiectomy in patients with metastatic HRPC found that 37.2% of 43 patients who showed a PSA reduction of 1 50% were treated with EMP, and that the decrease in PSA correlated signifi cantly with favorable cancer-specifi c survival. However, the median time to subjective progression and median overall survival did not differ signifi cantly between the EMP and placebo groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination therapies therefore appear superior for HRPC than EMP monotherapy based on both PSA levels and measurable disease response. A Danish study (DAPROCA study 9002) [12] of EMP versus placebo as second-line treatment after orchiectomy in patients with metastatic HRPC found that 37.2% of 43 patients who showed a PSA reduction of 1 50% were treated with EMP, and that the decrease in PSA correlated signifi cantly with favorable cancer-specifi c survival. However, the median time to subjective progression and median overall survival did not differ signifi cantly between the EMP and placebo groups.…”
Section: Discussionmentioning
confidence: 99%
“…Kelly et al [10] reported the prognostic value of several variables in relation to the survival of patients with HRPC, and found that posttreatment PSA decline was the most important parameter. Monitoring of PSA levels therefore represents a useful and relevant endpoint for clinical studies in this area [11,12] . In light of the paucity of reports on this topic, we carried out a prospective study to assess the effi cacy of EMP on patients with HRPC who showed an elevated PSA level following ADT, using changes in serum PSA as the major endpoint.…”
mentioning
confidence: 99%
“…As a single agent, the radiographic response rate of estramustine is only 5% to 19% [5•,6]. In a double-blind multicenter study, 131 patients with progressing metastatic hormone-refractory prostate cancer were randomized to receive 280 mg of estramustine phosphate twice daily versus placebo [7]. Breast tenderness, gynecomastia, and diarrhea were more frequent among patients in the estramustine phosphate group.…”
Section: Microtubule Antagonists and Estramustine Phosphate Combinationmentioning
confidence: 99%
“…In a randomized multicenter trial the Danish Prostatic Cancer Group [75] compared the effect of estramustine phospate to placebo as a supplement to standard palliative therapy for patients with HRPC. The selected dose of 560 mg/daily was lower than that used by others.…”
Section: Estramustinementioning
confidence: 99%